2014
DOI: 10.1007/s10653-014-9632-5
|View full text |Cite
|
Sign up to set email alerts
|

Phthalate esters in water and sediments of the Kaveri River, India: environmental levels and ecotoxicological evaluations

Abstract: Phthalate esters are well known for their environmental contamination and toxicological effects as "endocrine disruptors." In this study, environmental levels of phthalate esters and ecotoxicological risk assessments were performed in one of the major rivers in India, the Kaveri. Water and sediment samples were collected during 2010-2012 representing the major stretch of the river and extracted by solid-phase and ultrasonic methods, respectively, and analyzed for six major phthalates by using a gas chromatogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(66 citation statements)
references
References 43 publications
6
41
0
Order By: Relevance
“…The extensive use of PAE-containing products results in the release of large amounts of these compounds into the environment. It has been reported that the residues of PAEs were detected in various environmental matrices, such as air (Teil et al, 2006;Tran and Kannan, 2015), soil (Net et al, 2015;Niu et al, 2014), water and sediment (Peijnenburg and Struijs, 2006;Selvaraj et al, 2015). Researchers have indicated that some PAEs have endocrine disruptive effects in animals and humans (Main et al, 2006;Philippat et al, 2015;Zota et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The extensive use of PAE-containing products results in the release of large amounts of these compounds into the environment. It has been reported that the residues of PAEs were detected in various environmental matrices, such as air (Teil et al, 2006;Tran and Kannan, 2015), soil (Net et al, 2015;Niu et al, 2014), water and sediment (Peijnenburg and Struijs, 2006;Selvaraj et al, 2015). Researchers have indicated that some PAEs have endocrine disruptive effects in animals and humans (Main et al, 2006;Philippat et al, 2015;Zota et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…RQ due to remaining three phthalates (DEP, DBP and BBP) was below 1 confirming no harmful impacts. Selvaraj et al (2015) reported a RQ value of 43 for DEHP in Kaveri River of south India. The toxicity values (LC 50, 96 h, fish) of these four phthalates as derived from ECOSAR were also in accordance to obtained RQ values.…”
Section: Seasonal Influences On Removal Of Phthalatesmentioning
confidence: 99%
“…However, there are no reports available in literature that evaluated the temporal variation in risk of phthalates. Present studies reported only level of risk and exposure data such as Selvaraj et al (2015) and Das et al (2014) evaluated in Kaveri River of south India, and drinking water of north India, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Phthalate are becoming a great environmental concern because of their ubiquitous nature and studies have indicated various reproductive toxicities and carcinogenic potentials. Phthalates are now known to cause a broad range of birth defects and lifelong reproductive impairment in laboratory animals exposed in-utero (Ema et al, 1998; Wine et al, 1997; Gray et al, 1999).Phthalates have been found virtually in all compartments of the environment including fresh water (Tan 1995;Selyarai et al, 2015; DominguezMorueco et al, 2014; Liu et al, 2015; Liu et al, 2014;Gao and Wen 2016), lake sediments, buried PVC, landfill leachates, atmospheric aerosols (Simoneitet al, 1988), in rain water (Simoneit and Mazurek, 1989). Reports showed that, in river water DEHP, DBP, diisobutyl phthalate (DIBP) and DEP were found in all samples, with DEHP as the dominant compound with concentrations of up to 10 µg/l and a mean value of 1 µg/l for the River Rhine(Furtmann 1994).…”
mentioning
confidence: 99%
“…Phthalates have been found virtually in all compartments of the environment including fresh water (Tan 1995;Selyarai et al, 2015;DominguezMorueco et al, 2014;Liu et al, 2015;Liu et al, 2014;Gao and Wen 2016), lake sediments, buried PVC, landfill leachates, atmospheric aerosols (Simoneitet al, 1988), in rain water (Simoneit and Mazurek, 1989). Reports showed that, in river water DEHP, DBP, diisobutyl phthalate (DIBP) and DEP were found in all samples, with DEHP as the dominant compound with concentrations of up to 10 µg/l and a mean value of 1 µg/l for the River Rhine (Furtmann 1994).…”
mentioning
confidence: 99%